International survey of neuromonitoring and neurodevelopmental outcome in children and adults supported on extracorporeal membrane oxygenation in Europe. (March 2023) - Cvetkovic, Mirjana; Chiarini, Giovanni; Belliato, Mirko; Delnoij, Thijs; Zanatta, Paolo; Taccone, Fabio Silvio; Miranda, Dinis dos Reis; Davidson, Mark; Matta, Nashwa; Davis, Carl; IJsselstijn, Hanneke; Schmidt, Matthieu; et al.
Background: Adverse neurological events during extracorporeal membrane oxygenation (ECMO) are common and may be associated with devastating consequences. Close monitoring, early identification and prompt intervention can mitigate early and late neurological morbidity. Neuromonitoring and neurocognitive/neurodevelopmental follow-up are critically important to optimize outcomes in both adults and children. Objective: To assess current practice of neuromonitoring during ECMO and neurocognitive/neurodevelopmental follow-up after ECMO across Europe and to inform the development of neuromonitoring and follow-up guidelines. Methods: The EuroELSO Neurological Monitoring and Outcome Working Group conducted an electronic, web-based, multi-institutional, multinational survey in Europe. Results: Of the 211 European ECMO centres (including non-ELSO centres) identified and approached in 23 countries, 133 (63%) responded. Of these, 43% reported routine neuromonitoring during ECMO for all patients, 35% indicated selective use, and 22% practiced bedside clinical examination alone. The reported neuromonitoring modalities were NIRS ( n = 88, 66.2%), electroencephalography ( n = 52, 39.1%), transcranial Doppler ( n = 38, 28.5%) and brain injury biomarkers ( n = 33, 24.8%). Paediatric centres (67%) reported using cranial ultrasound, though the frequency of monitoring varied widely. Before hospital discharge following ECMO, 50 (37.6%) reported routine neurological assessment and 22 (16.5%) routinely performed neuroimaging with more paediatric centres offering neurological assessment (65%) as compared to adult centres (20%). Only 15 (11.2%) had a structured longitudinal follow-up pathway (defined followup at regular intervals), while 99 (74.4%) had no follow-up programme. The majority ( n = 96, 72.2%) agreed that there should be a longitudinal structured follow-up for ECMO survivors. Conclusions: This survey demonstrated significant variability in the use of different neuromonitoring modalities during and after ECMO. The perceived importance of neuromonitoring and follow-up was noted to be very high with agreement for a longitudinal structured follow-up programme, particularly in paediatric patients. Scientific society endorsed guidelines and minimum standards should be developed to inform local protocols.